The Improvement of The Students' Vocabulary by Using Crossword Puzzle - Agus Akmad Rifai; Siminto Siminto; Akhmad Ali Mirza (Journal of English Language Learning, 2023)
This study aims to help overcome the problems that exist in class VII B students of SMPN 1 Jabiren Raya, Pulang Pisau Regency, Jabiren Raya District. A total of 30 students were the subjects in this study. After conducting a pre-observation, a problem was found, namely related to the vocabulary that students still have a little. Therefore, to overcome this problem, the researcher used Crossword Puzzle printed on HVS paper as a method to help improve students' vocabulary. This research uses Classroom Action Research (CAR) method. This research design uses collaborative classroom action research. This study collaborated with the English teacher of SMPN 1 Jabiren Raya as a collaborator and observer. The model in this study uses the Kurt Lewin Model where the stages in each cycle begin with the stages of Planning, Action, Observation, and Reflection. This study consisted of two cycles in which in each cycle there was 1 meeting with a duration of 3 subject hours. To collect data, researchers used research instruments: Vocabulary Test, Interview, and Questioner. After the implementation of this research, there was an increase in students’ vocabulary. It can be seen from the increase in each cycle, namely in cycle 1 students got 53.3% classical completeness and increased in cycle 2 to 90% after conducting vocabulary tests through multiple choice. Therefore, based on the research that has been conducted, the Crossword Puzzle method can improve students' vocabulary.